KARAKTERISTIK PERSONAL, MORALITAS PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Asbi Amin; Wahyuni (eBA Journal: Journal Economic, Bussines dan Accounting, 2021)
This reserach intends to examine individual characteristics, tax morale and tax sanctions have an influence on taxpayer compliance. This research is a quantitative research. The population in this study were individual taxpayers at West Makassar Tax Office using Accidental sampling technique so that the sample amounted to 100 people. The data were collected by using a questionnaire method. The analysis method used in testing the hypothesis is multiple linear regression analysis. The results prove that individual characteristics, tax morale and tax sanctions have a positive and significant effect on taxpayer compliance.